Autoimmune brainstem encephalitis: Clinical associations, outcomes, and proposed diagnostic criteria - Michael Gilligan; Smathorn Thakolwiboon; Emma Orozco; Samantha Banks; Eoin P. Flanagan; Sebastian Lopez‐Chiriboga; Jan‐Mendelt Tillema; John R. Mills; Sean J. Pittock; Cristina Valencia Sanchez; Anastasia Zekeridou; Divyanshu Dubey; et al. (Annals of Clinical and Translational Neurology)
Abstract Objective We describe neurologic phenotype, clinical associations, and outcomes in autoimmune brainstem encephalitis. Methods Medical records of neural‐IgG positive autoimmune brainstem encephalitis patients diagnosed at Mayo Clinic (January 1, 2006–December 31, 2022) were reviewed. Results Ninety‐eight patients (57 male) were included. Median age of symptom onset was 51 years (range, 8 months‐85 years). Frequent presenting features were ≥1: diplopia (80%), ataxia (78%), dysarthria (68%), vestibulocochlear symptoms (67%), dysphagia (61%), nausea/vomiting (42%), and facial weakness (32%). Altered mental status (11%) was uncommon. Neural antibodies detected were as follows: KLHL‐11 (26 patients), GAD65 (high titer, 12), ANNA‐1 (anti‐Hu, 8), ANNA‐2 (anti‐Ri, 8), Ma2 (7), IgLON‐5 (6), AQP4 (6), MOG (4), glycine receptor (4), GQ1B (4), PCA‐1 (anti‐Yo, 4), DPPX (2), neurochondrin (2), neurofilament (2), NMDA‐R (2), AGNA‐1 (SOX‐1, 1), ANNA‐3 (DACH1, 1), amphiphysin (1), CRMP‐5 (1), ITPR‐1 (1), PCA‐Tr (DNER, 1), and PDE10A (1). Cancer was identified in 55 patients: germ cell (23 patients; 3 extra‐testicular), ductal breast adenocarcinoma (8), small cell carcinoma (6, lung 4), adenocarcinomas (6), neuroendocrine carcinoma (3), hematologic (2), squamous cell (2), and other (7). Median modified Ranking score (mRS) at last follow‐up was 3 (range, 0–6). Factors associated with poor outcome included abnormal brain MRI, bulbar symptoms, and elevated CSF IgG index. Kaplan–Meier analysis revealed faster progression to wheelchair in patients who were immunotherapy refractory and with elevated CSF IgG index. Diagnostic criteria for autoimmune brainstem encephalitis (definite and probable) are proposed. Interpretation Autoimmune brainstem encephalitis is a distinct clinical subphenotype of autoimmune encephalitis. Abnormal brain MRI, bulbar symptoms, and elevated CSF‐IgG index associate with poor outcome.